Production Capacity and Workstations Load in the Animal Feed Production Process (Agricultural Engineering, 2016)
Production capacity is the amount of production with the determined assortment structure possible to achieve by a particular production unit in a determined time at the optimal use of production factors and at maintaining the products quality corresponding to standards. The objective of the paper was to determine the production power and output of particular workstations which constitute an assembly line of dry animal feed. The scope of research covered an assembly line in the establishment which produces dry feed for pet animals. Based on information and documentation obtained from the company manager and on the work schedule determined for particular workstations, the operation time of a machine, human work time (operation of a machine) and operation time of the entire station with its working surface was determined. Research showed that workstations which constituted the assembly line of dry animal feed were loaded within 76 to 86%. The lowest loading was reported in the mill and LP02 assembly line and it was respectively 76 and 78%. Whereas loading of the remaining devices was comparable and was at the level within 84 to 86%.